2011
DOI: 10.1016/j.econmod.2011.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Income insurance and the determinants of income insurance via foreign asset revenues and foreign liability payments

Abstract: We document that the net factor income smoothing channel in OECD countries is primarily driven by net financial asset income, while the other two sub-components (net compensation of employees, net taxes on imports) turn out to be ineffective. Once factor income inflows are distinguished from outflows, empirical evidence suggests a non-significant effect of inflows in terms of income smoothing as opposed to a positive and significant role of factor income outflows (18 percent for the EMU and 16 percent for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
(13 reference statements)
2
13
0
Order By: Relevance
“…The sample is divided into several country groups: EMU, EU, new EU and OECD countries -see Table 1 for the complete country list. Our country selection and data coverage are comparable to those of Sørensen et al (2007), Demyanyk et al (2008) and Balli et al (2011). Per capita figures are obtained by normalizing over the population of each country.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample is divided into several country groups: EMU, EU, new EU and OECD countries -see Table 1 for the complete country list. Our country selection and data coverage are comparable to those of Sørensen et al (2007), Demyanyk et al (2008) and Balli et al (2011). Per capita figures are obtained by normalizing over the population of each country.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…They notice that the effect of diversification on risk-sharing is roughly similar for foreign assets and liabilities. Balli et al (2011), on the contrary, find that increased holdings of foreign assets caused income dis-smoothing during [2001][2002][2003][2004][2005][2006][2007], the years surrounding the introduction of the Euro. They interpret their result as a consequence of increased business cycle synchronization across EMU and EU countries.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, risk-sharing channels have been quantified in a number of works. Sørensen and Yosha (1998) found that the bulk of consumption risk sharing is provided by procyclical saving channels, and recent studies (Sørensen et al, 2007;Balli et al, 2011Balli et al, , 2013Balli et al, , 2014Balli and Rana, 2015) have documented the importance of the net factor income channel (net asset revenues) on the extent of the risk sharing.…”
Section: Introductionmentioning
confidence: 99%
“…Balli et al (2010b) andBalli et al (2011) also followedSørensen et al (2007) and found that the extent of income smoothing through net factor income flows and the amount of the foreign asset holdings do not have a strong relationship.…”
mentioning
confidence: 98%